Control of Dynamic Performance Through Feedback Converter SSC In Grid Integrated Wind Energy System - Rani, Preeti; Arora, Ved Parkash; Sharma, Naveen Kumar (Distributed Generation & Alternative Energy Journal, 2022)
A feedback converter-based Static series compensator (FBC-SSC) is a device that can simultaneously compensate for currents and voltages in a distribution network to enhance the Power Quality (PQ) in Grid integrated Energy System (GIWES). PQ is a term that refers to the conjunction of voltage and current stability. Electronically operated and non-linear gadgets with significant applicability in distribution networks and enterprises have become significant aspects due to PQ constraints such as imbalance voltage and frequency, and transients. Improved hysteresis-based FBC-SSC is suggested in this study for optimizing PQ in GIWES. The novelty in this research is improved hysteresis or hybrid PI and PWM-based hysteresis controlled FBC-SSC. In a wind turbine generation system, improved hysteresis based is used to find the gate trigger pulse for SSC. The suggested controller, when combined with FBC-SSC, improves the WES dynamic performance. Simultaneously, the grid network can compensate for current and voltage irregularities in nearby terminals. All converters in the proposed topology share a standard dc-link capacitor. As a result, power can be transmitted from one distributor to another. The proposed topology is modelled in the MATLAB/SIMULINK environment. The effectiveness research is performed using the improved hysteresis controller. Finally, the obtained results are compared to two existing controllers: a Proportional Integral controller and a traditional Pulse Width Modulation (PWM) controller. As a consequence, the performance level can show that the advised technique is effective. When compared to another typical control approach, the suggested system obtains remarkably low THD values of 0.94 percent.